Chalcone- and flavone-based novel terpyridine metal complexes: Synthesis, electrochemical, photophysical, photovoltaic and computational studies. (May 2022) - Mughal, Ehsan Ullah; Obaid, Rami J.; Sadiq, Amina; Alsharif, Meshari A.; Naeem, Nafeesa; Kausar, Samia; Altaf, Ataf Ali; Jassas, Rabab S.; Ahmed, Safeer; Alsantali, Reem I.; Ahmed, Saleh A.
Abstract: In the present protocol, a series of varyingly substituted terpyridine-based ligands have been designed and synthesized through a well-known Kröhnke reaction. Their binding behavior was evaluated with the library of metal cations. Their complexation with Ru(II), Fe(II), Co(II) and Zn(II) led to interesting coordination compounds with fascinating spectroscopic and electrochemical properties. The structural elucidation of all the newly synthesized ligands was accomplished by UV–Vis, FT-IR and 1 H and 13 C NMR spectroscopic techniques and the complexes were characterized by UV–Vis, FT-IR, 1 H and 13 C NMR and MALDI-TOF mass spectrometry. Their absorption behavior in dilute solutions was investigated in order to elucidate the structure-property relationship and demonstrate the effect of the nature of different aryl-substituents on the terpyridine scaffold as well as a decisive role of metal on the complexes. Likewise, the electrochemical behavior of these complexes (C 1 –C 9 ) at a platinum electrode was analyzed by cyclic voltammetry and investigated at 200, 100 and 40 mVs −1 in acetonitrile (CH3 CN). These complexes showed a quasi-reversible redox reaction. The oxidation-reduction reactive sites of these derivatives were located via geometry optimization using density functional theory (DFT) at the B3LYP/3-21g in the Guassian-09 level of theory. Remarkably, the most important contribution of this paper is the presentation of an entirely new group of terpyridine-based metallic dyes (chalcone- and flavone-based) and exploration of those dyes in the fabrication of Dye-Sensitized Solar Cells (DSSCs). DSSCs were constructed using these dyes and their efficiency was investigated by means of photovoltaic measurements. Results demonstrate that electron-donating substitutions provide better photovoltaic parameters on the ZnO surface as compared to electron-withdrawing groups. A detailed structure-property relationship has been established based on optical, electrochemical and photovoltaic properties studies. All experimental results were reinforced by computational approaches. Graphical abstract: Image 1 Highlights: 2, 2′:6′, 2″- Tpy and its derivatives represent highly versatile ligands for the complexation of transition metal ions. The utilization of terpyridines in device chemistry has exploded such as in DSSCs. We have evaluated these terpyridine-based metallic dyes for DSSCs. The EDGs provide better photovoltaic parameters onto the ZnO surface as compared to EWGs. The experimental parameters are in good agreement with theoretical data.